2012
DOI: 10.1152/ajpheart.00500.2011
|View full text |Cite
|
Sign up to set email alerts
|

Histamine induces activation of protein kinase D that mediates tissue factor expression and activity in human aortic smooth muscle cells

Abstract: Hao F, Wu DD, Xu X, Cui M. Histamine induces activation of protein kinase D that mediates tissue factor expression and activity in human aortic smooth muscle cells. Am J Physiol Heart Circ Physiol 303: H1344 -H1352, 2012. First published September 21, 2012; doi:10.1152/ajpheart.00500.2011.-Histamine, an inflammatory mediator, has been shown to influence the pathogenesis of vascular wall cells. However, the molecular basis of its influence is not well understood. Our data reveal that histamine markedly induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…PKD has already been implicated in pathological vascular hypertrophy by inactivating the histone deacetylase HDAC5 (Xu et al ., ) and promoting vascular smooth muscle cell proliferation by ERK5 and c‐Fos activation (Geng et al ., ). Furthermore, increased phosphorylation of p38 MAPK could be mediated by PKD (Hao et al ., ). Finally, activation of p38 could additionally lead to attenuated cAMP formation in hPASMC (El‐Haroun et al ., ), a contributing mechanism in NPY vasoconstrictive action.…”
Section: Discussionmentioning
confidence: 99%
“…PKD has already been implicated in pathological vascular hypertrophy by inactivating the histone deacetylase HDAC5 (Xu et al ., ) and promoting vascular smooth muscle cell proliferation by ERK5 and c‐Fos activation (Geng et al ., ). Furthermore, increased phosphorylation of p38 MAPK could be mediated by PKD (Hao et al ., ). Finally, activation of p38 could additionally lead to attenuated cAMP formation in hPASMC (El‐Haroun et al ., ), a contributing mechanism in NPY vasoconstrictive action.…”
Section: Discussionmentioning
confidence: 99%
“…Lahouaria Hadri et al reported that histamine enhances the promoter activity and expression of SERCA 3 gene via H1 receptor by Ca 2+ -calcineurin pathway in HUVEC-derived EA.hy926 cells [51]. Further studies suggested that PKD and ERK are downstream targets of PLC-PKC to play a role in histamine signaling pathway because (1) histamine induces tissue factor expression via H1 receptor to activate PKC-PKD phosphorylation in smooth muscle cells [52], (2) histamine induces the expression of early growth response factor 1 (Egr-1) by PKC-ERK, and (3) ERK is essential for histamine-induced cytokine production [53, 54]. Our data indicate that TR3-TV2 and TR3-TV3 are regulated by PLC/Ca 2+ /calcineurine/PKC/PKD/ERK signaling pathway via G protein-coupled histamine receptor H1.…”
Section: Discussionmentioning
confidence: 99%
“…Identifikacija subtipova histaminskih receptora u ljudskom srcu i endotelnim ćelijama obezbeđuje bolje razumevanje uloge histamina u patofiziologiji kardiovaskularnog sistema i doprinosi novom pristupu histaminom izazvanoj srčanoj disfunkciji. Tako, histamin indukuje hiperplaziju intime i promoviše formiranje aterosklerotskih lezija [11], povećava ekspresiju i aktivaciju tkivnog faktora koji je ključni inicijator koagulacije krvi [12] i povećava vaskularnu peremeabinost za LDL [13]. Antagonisti H 1 receptora mogu da imaju kardiotoksični efekat i da inhibiraju repolarizaciju K+ kanala (posebno Ikr) što dovodi do prolongiranja akcionog potencijala [14].…”
Section: Uvodunclassified